Description of knowledge and attitude about free sex in adolescent in kendari city - lestari, hariati; Imran Ahmad, La Ode Ali (CORE JOURNAL, 2022)
Adolescence is a dynamic growth and development phase in life, a period of transition from childhood to adulthood marked by accelerated physical, mental, emotional and social development, making it vulnerable to reproductive health disorders. The purpose of this study was to describe knowledge and attitudes about free sex among adolescents in the city of Kendari in 2021. This quantitative research was carried out using a descriptive approach. A total of 223 samples were selected by purposive sampling technique. The results showed that most of the adolescents in Kendari had good knowledge and attitudes regarding free sex. Even so, it needs routine education, parental control and supervision at each phase of adolescent development.